Comfort feeding in hospitalised people with dementia: a retrospective study of survival following comfort feeding recommendations - Christine Davis; Nasime Mokari-Manshadi; Viviane De Menezes Caceres; Patrick Russell; Toby Gilbert; Stephen Hedger; Udul Hewage; Dirk Hoffman; Yogesh Sharma; Alice O’Connell; Amrit Sandhu; Jeff Faunt; et al. (The Journal of Nutrition, Health and Aging)
Objectives: Persistent and significant swallowing impairment can occur in individuals with dementia. Determining prognosis and establishing realistic goals of care in this population is complex and comfort feeding may be recommended. This study aimed to establish evidence relating to patient outcomes following recommendation of comfort feeding to aid informed decision making. Design: A multi-centre, retrospective audit was conducted for a two-year period to establish the survival and readmission rates for hospitalised people with dementia, following recommendation of a comfort feeding plan. Setting: The study was conducted at three acute care hospitals in Adelaide, South Australia. Participants: A total of 163 participants were included, 90 male and 73 female, with a median age of 88 years. Measurements: Mortality within 30 and 90 days of admission and readmission rates within 30 days of discharge were calculated. Results: Forty-two percent of participants died during the admission during which a comfort feeding plan was recommended. Overall median survival time and one month survival was 13 days and 25%, respectively. Readmission rates were low (7.4% of those discharged). Comfort feeding recommendations aligned with dysphagia severity and those for whom Nil By Mouth (NBM) or ice chips only were recommended were at highest risk of dying in hospital, those recommended thickened fluids +/− ice chips were most likely to be alive 30 days after their original admission date. Conclusion: Dementia and comfort feeding were associated with high mortality rates, high rates of discharge to a supportive care facility and low readmission rates. Dysphagia severity associated with the consistency of fluids recommended.